2016
DOI: 10.1016/j.nbd.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adeno Associated Viral (AAV) vector type 9 delivery of Ex1-Q138-mutant huntingtin in the rat striatum as a short-time model for in vivo studies in drug discovery

Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder characterized by dyskinesia, cognitive impairment and emotional disturbances, presenting progressive neurodegeneration in the striatum and intracellular mutant Huntingtin (mHTT) aggregates in various areas of the brain. Recombinant Adeno Associated Viral (rAAV) vectors have been successfully used to transfer foreign genes to the brain of adult animals. In the present study we report a novel in vivo rat HD model obtained by stereotaxic injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…However, features of movement disorder were different to that of N171-82Q Tg mice (expressing a mutant N-terminal fragment of HTT ), which displayed loss of coordination, hunched posture, tremors, abnormal gait, and clasping of hindlimbs (Schilling et al, 1999 ). In the present study, HTT aggregates were observed only in the striatum, similar to the in vivo rat HD model obtained by stereotaxic injection of AAV serotype nine containing Exon1-Q138 mutant HTT (AAV-9-Q138) (Ceccarelli et al, 2016 ). However, the expression pattern was different to that of N171-82Q Tg mice (Schilling et al, 1999 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, features of movement disorder were different to that of N171-82Q Tg mice (expressing a mutant N-terminal fragment of HTT ), which displayed loss of coordination, hunched posture, tremors, abnormal gait, and clasping of hindlimbs (Schilling et al, 1999 ). In the present study, HTT aggregates were observed only in the striatum, similar to the in vivo rat HD model obtained by stereotaxic injection of AAV serotype nine containing Exon1-Q138 mutant HTT (AAV-9-Q138) (Ceccarelli et al, 2016 ). However, the expression pattern was different to that of N171-82Q Tg mice (Schilling et al, 1999 ).…”
Section: Discussionsupporting
confidence: 87%
“…Presently, recombinant AAVs are one of the preferred vectors, because their stable transduction of dividing and non-dividing cells, strong neural tropism, low risk of insertional mutagenesis, and reduced immune responses (Blessing and Déglon, 2016 ; Grieger et al, 2016 ; Saraiva et al, 2016 ). According to many studies that measured the ability of AAV serotypes to target the CNS, when administrated into the brain parenchyma of rodents, most of the serotypes (1, 2, 4, 5, 8 and 9) transduced neurons and glia in the CNS areas including striatum, hippocampus and neocortex (Ruiz and Déglon, 2012 ; Watakabe et al, 2015 ; Ceccarelli et al, 2016 ; Saraiva et al, 2016 ). Other serotypes, such as AAV-DJ, are potentially useful but have been less well examined (Cearley and Wolfe, 2006 ; Klein et al, 2008 ; Aschauer et al, 2013 ; Holehonnur et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral vectors may be used as well for siRNA delivery, which have the advantage of being able to directly target the nucleus, and such an approach has been used in animal models of Huntington’s disease and amyotrophic lateral sclerosis [173175]. Intraparenchymal injections have been utilized in rat and non-human primate models of Huntington’s disease to delivery these viral vectors [176, 177]. Other strategies to transiently increase BBB permeability have been investigated as well including a variety of different compounds and most recently focused ultrasound [178182].…”
Section: Therapeutic Strategies Targeting Pathological Taumentioning
confidence: 99%